REINTERPRETATION THE HADITH ON MARRIAGE PREFERENCES FROM GADAMER'S HERMENEUTICS PERSPECTIVE: Integrating Textual Meaning and Contemporary Social Relevance - PK, Moh. Nurun Alan Nurin; Qudsia, Miatul; Irfani, Muhammad Syahru (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2025)
The hadith regarding preferences in choosing a life partner, which states,